2007
DOI: 10.1007/s12122-007-9033-y
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and International Migration: An Option Cum Portfolio Model

Abstract: Migration, Family, Risk diversification, Option value, D81, F22,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…Therefore an hysteresis process increases duration of immigrants. 15 The mashallian trigger is "the point at which the present value of the benefit exceed the cost of migration", see Anam et al (2007). 16 These comparative statics happen in both the cases, with or without community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore an hysteresis process increases duration of immigrants. 15 The mashallian trigger is "the point at which the present value of the benefit exceed the cost of migration", see Anam et al (2007). 16 These comparative statics happen in both the cases, with or without community.…”
Section: Discussionmentioning
confidence: 99%
“…Many works in economic literature view migration as permanent 1 . The fact that the migration decision is in many cases at least partially irreversible, added to uncertainty over the wage differentials and the economic conditions in the host country 2 , that push the postponable migration choice, is an important element that enabled Burda (1995) to adapt the real option approach to migration decision assumed, in line with Sjaastad (1962), as an investment decision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while a variety of studies have analysed the effect of uncertainty on migration behaviour-such as the literature following Burda's (1993;1995) works on the "option value of waiting", which links the investment literature of Pindyck and Dixit (see Dixit, 1992;Dixit and Pindyck, 1994;Pindyck, 1991) to migration decisions (see O'Connell, 1997;Locher, 2001;Wang and Wirjanto, 2004;Anam, Chiang, & Hua, 2008, to name just a few), or papers on the effects of individual risk attitudes on migration decisions (see Heitmueller, 2005;Kan, 2003)-this literature has not considered cross-border commuting as an alternative to migration though commuting plays an important role in border regions between European Union (and neighbouring non-EU) countries.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, Burda (1995), showed that individuals prefer to wait before migrating, even if the present value of the wage differen-tial is positive, because of the uncertainty and the sunk costs associated with migration. Subsequently Khwaja (2002) and Anam et al, (2007) developed Burda's approach by describing the role of uncertainty in the migration decision. Another work that uses real option in migration is Feist (1998), in which the author analyses the option value of the low-skilled workers to escape to the unofficial sector if welfare benefits come too close to the net wage in the official sector.…”
Section: Introductionmentioning
confidence: 99%